The Effect of Two Denture Adhesives on Maxillary Complete Denture Dislodgement. A Pilot Study - Mujahed T. Qasim; Munther N. Kazanji (University of Mosul, College of Dentistry, 2015)
Aim: The purpose of this study was to evaluate the effect of two denture adhesives on incisal bite force until denture dislodgement without and with the adhesive. This in-practice study assessed also patients' perception regarding the use of adhesive. Materials and Methods: A total of 6 patients )2 men, 4 women( who wore complete maxillary and mandibular dentures were tested for denture performance both without and with denture adhesive. A locally constructed digital biting force device was used to measure the incisal bite force. Two adhesives pastes )Kin oro and Bony plus( were used in the study. Patients were asked to bite on the digital biting force device and the readings of incisal bite force were recorded. Patient perceptions )instant perception and delayed perception( after 1 week of using the denture adhesive were also assessed by a questionnaire and analyzed for denture performance on chewing and mastication, retention and fitness, confidence, comfort, and speaking. Results: The result showed that denture adhesives improved the incisal bite force of complete denture wearers significantly. The incisal bite force )in kg( )mean : without adhesive 1.78, with Kin oro 3.04, and with Bony plus 3.21(. There was an improvement in chewing and mastication, retention and fitness, confidence, comfort, and speaking after using both types of denture adhesives. Conclusions: The use of denture adhesive was found to be significantly effective in improving the incisal bite force of complete dentures until the dislodgement of upper denture. Bony plus paste adhesive was found to be more effective than Kin oro paste. Subjectively, the patients reported an improved perception of denture performance and that the use of adhesive provided greater confidence when using the prosthesis